A statistical approach on dissimilarities of elderly population and the elderly population live in elderly homes, Sri Lanka - Senanayake, S.G.N.C. (My University, 2019)
Sri Lanka is experiencing a period of rapid aging, which increases the need of long-term care services in the country. Elderly homes have been the traditional alternative to deal with the increase of elderly population in the country, with services supplied by a mix of for-profit and nonprofit providers. Additionally, population exhibits a high degree of geographical concentration. The study aims to identify the determinants of the geographical location of elderly population live in elderly homes in Sri Lanka. The analysis takes into account the different location criteria for different types of nursing homes as well as potential spatial effects. The paper uses spatial and statistical analysis tools to identify concentration of elderly population and population characteristics and to estimate the determinants of nursing homes availability and coverage in the country. The analysis–based on Dissimilarity Index, Location Quotient and location coefficient and Anova test- show the existence of clusters of nursing homes according to elderly population. Both anova test and Dissimilarity index reveals a spatial inequality of the distribution of elderly population as well as the population in elder homes. Further, the Location Quotient results demonstrates a different level of concentration of elderly population in the elderly homes compare to the overall distribution of elderly population. Whereas Anuradhapura, Kurunegala, Kaluthara, Rathnapura and Galle demonstrates the highest values for the elderly home population. The results reveals the importance of the regional development of elderly homes with professional care givers.
Keywords: elderly population; elderly homes; Sri Lanka